Inhibition of Salmonella enterica serovars by microcin J25 - Vincent, Paula Andrea (2004)
Escherichia coli microcin J25 (MccJ25) is a 2107-Da peptide antibiotic whose uptake into E. coli is mediated by the outer-membrane receptor FhuA and the inner membrane proteins TonB, ExbB, ExbD, and SbmA. A survey of the sensitivity of several Salmonella enterica serovars showed that the antibiotic was highly active against some serovars, while S. Typhimurium, S. Derby, and some S. Enteritidis strains were completely resistant. Resistant strains became hypersensitive to MccJ25 when given the fhuA gene of E. coli, indicating that insensitivity is due to the inability of the FhuA protein to mediate penetration of MccJ25. Whereas in E. coli MccJ25 targets RNA polymerase, in S. Typhimurium it inhibits not only RNA synthesis but also cell respiration. Fluorescence viability staining showed that S. Typhimurium cells exposed to MccJ25 remain viable but are unable to form colonies.